Recent Progress on Graft Polymerization of Natural Polymer Flocculants: Synthesis Method, Mechanism and Characteristic - Tang, Xiaomin; Jiang, Xue; Zhang, Shixin; Zheng, Huaili; Tan, Xuemei (Mini-Reviews in Organic Chemistry, 2018)
Natural polymer flocculants (NPF) and their derivatives as the eco-friendly, nontoxic and biodegradable materials have attracted significant attention in water treatment. The graft polymerization of NPF and its synthesis mechanisms that have been proposed in the literature are mainly reviewed in this paper. Initiation system is the key factor in the modification of NPF and it influences the characteristics of copolymer in terms of grafting efficiency, grafting percentage, molecular weight and cationic degree. Reaction time, reaction temperature and the molar ratio of monomer to NPF affect the synthesis of NPF as well. The modified NPF possessing the higher molecular weight and cationic degree contributes to the better coagulation-flocculation performance. The solubility of NPF is improved after grafting monomer onto the NPF backbone.
Keywords: redox initiation